2018
DOI: 10.1007/s11908-018-0640-y
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma urealyticum: the Role as a Pathogen in Women’s Health, a Systematic Review

Abstract: A systematic review was performed. Searching PUBMED and EMBASE for published articles from January 2003 to September 2017 using the key word "Ureaplasma urealyticum" yielded 1835 manuscripts. These were further screened using defined inclusion criteria: (1) original peer-reviewed observational studies; (2) English language; (3) U. urealyticum was specifically isolated; (4) present "cases"/"exposed" and "controls"/"unexposed" to enable calculating an association between U. urealyticum and the outcome studied. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
5
10
1
Order By: Relevance
“…In this study, UU was detected in 62.04% of the 6190 enrolled women, CT was found in 10.20% of the 11 242 enrolled women, and NG was isolated in 4.09% of the 8289 enrolled women. Compared with region‐based data on the worldwide population, the infection rate of UU (62.04%) in the present study was higher than rates reported in a meta‐analysis (1%‐62%), but was similar to the rate in Changzhou (60.11%), which is another region in China. Because of the high infection rate of UU in Taizhou area, clinicians should carry out routine testing for UU in high‐risk women, including women infected with other STI agents, symptomatic women with cervicitis, urethritis and other gynecological diseases, women planning for pregnancy, and sex workers.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In this study, UU was detected in 62.04% of the 6190 enrolled women, CT was found in 10.20% of the 11 242 enrolled women, and NG was isolated in 4.09% of the 8289 enrolled women. Compared with region‐based data on the worldwide population, the infection rate of UU (62.04%) in the present study was higher than rates reported in a meta‐analysis (1%‐62%), but was similar to the rate in Changzhou (60.11%), which is another region in China. Because of the high infection rate of UU in Taizhou area, clinicians should carry out routine testing for UU in high‐risk women, including women infected with other STI agents, symptomatic women with cervicitis, urethritis and other gynecological diseases, women planning for pregnancy, and sex workers.…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore, CT was significantly associated with UU and NG, whereas no association between NG and UU was found. study was higher than rates reported in a meta-analysis (1%-62%), 9 but was similar to the rate in Changzhou (60.11%), 10 women, including women infected with other STI agents, symptomatic women with cervicitis, urethritis and other gynecological diseases, women planning for pregnancy, and sex workers. However, part of women colonized with UU would not develop disease, and routine treatment in these asymptomatic women for UU might result in antimicrobial resistance; therefore, clinicians are more difficult to make therapy decision for asymptomatic women.…”
Section: The Co-infection Of Uu Ct and Ngsupporting
confidence: 68%
“…U. urealyticum is frequently found in the genital tract and normally elicits a response from the humoral immune system [1,4]. Deficits in this type of response are a risk factor for septic arthritis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Ureaplasma urealyticum , a short intra- and extracellular rod lacking a cell wall, frequently colonizes the genital human tract. In the genital tract of sexually active healthy women, prevalence estimates range from 38 to 75% [ 1 , 2 ]. This germ belongs to the genital mycoplasmas, containing Ureaplasma spp .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation